Changes in Lipid Profile of Keratinocytes from Rat Skin Exposed to Chronic UVA or UVB Radiation and Topical Application of Cannabidiol - Wojciech Łuczaj; Maria do Rosário Domingues; Pedro Domingues; Elżbieta Skrzydlewska (MDPI AG, 2020)
UV radiation is a well-established environmental risk factor known to cause oxidative stress and disrupt the metabolism of keratinocyte phospholipids. Cannabidiol (CBD) is a phytocannabinoid with anti-inflammatory and antioxidant effects. In this study, we examined changes in the keratinocyte phospholipid profile from nude rat skin exposed to UVA and UVB radiation that was also treated topically with CBD. UVA and UVB radiation promoted up-regulation of phosphatidylcholines (PC), lysophosphatidylcholines (LPC), phosphatidylethanolamines (PE) and down-regulation of sphingomyelin (SM) levels and enhanced the activity of phospholipase A2 (PLA2) and sphingomyelinase (SMase). Application of CBD to the skin of control rats led to down-regulation of SM and up-regulation of SMase activity. After CBD treatment of rats irradiated with UVA or UVB, SM was up-regulated and down-regulated, respectively, while ceramide (CER) levels and SMase activity were down-regulated and up-regulated, respectively. CBD applied to the skin of UV-irradiated rats down-regulated LPC, up-regulated PE and phosphatidylserines (PS) and reduced PLA2 activity. In conclusion, up-regulation of PS may suggest that CBD inhibits their oxidative modification, while changes in the content of PE and SM may indicate a role of CBD in promoting autophagy and improving the status of the transepidermal barrier.